PENGABDIAN MASYARAKAT DENGAN PEMBUATAN BANK AIR SEBAGAI KONSERVASI AIR TANAH DI PERUMAHAN PANCA ARGA - Yuwono Yuwono; Paulina Siregar; Syarifuddin Syarifuddin; Dewi Okta Pusparini (JURNAL NAGARA BHAKTI, 2025)
The Magelang Regency area and its surroundings are currently developing into a center of economy, education, and socio-cultural activities, with a rapidly increasing demand for drinking water. The challenge of water supply is becoming greater due to population growth and unpredictable climate conditions, which have resulted in an imbalance of water resources. At the Military Academy (Akmil) in Magelang, as a center for military education, there are now serious challenges related to clean water deficits caused by the rising daily water demand, reaching the maximum capacity of 3,500 people. Although the area is traversed by the Baben River, which never dries up, the geological condition of low-permeability soil located between four active volcanoes hinders the natural infiltration of rainwater. To address this challenge, the Military Academy has carried out a community service program by developing a Water Bank, which injects water from the Baben River into the ground as an effort to conserve groundwater. The Water Bank functions to collect and store excess rainwater or surface runoff into aquifers through infrastructures such as sedimentation tanks, water channels, and recharge wells. The water stored underground can be utilized during the dry season, thereby helping to ensure water security, prevent clean water shortages, and reduce the risk of flooding caused by stormwater runoff.